Polymeric Complex of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) with Schiff Bases Derived from Hydroquinone bis-(Acetylhydrazide) and Aromatic Aldehydes - BHANDARI, N.S.; Vivekanand, (Asian Journal of Chemistry, 2010)
Complexes of the general formula, M[C6H4{OCH2C(O) NH(N)=CHR}2 (AcO)2]n [where M = Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) and R = -C6H4OH, -C6H4CH3 and -C6H5] were prepared by the reaction of divalent metal acetates with respective hydroquinone bis-(acetylhydrazide-2-arylaldehyde). These complexes have been characterized on the basis of the elemental analysis, magnetic susceptibility and infrared spectral studies. The magnetic moment data indicate an octahedral geometry for the metal complexes.